Andrology on the Internet: Most wanted, controversial and often primary source of information for patients. (25th August 2017) - Baunacke, M.; Groeben, C.; Borgmann, H.; Salem, J.; Kliesch, S.; Huber, J.
Summary: The Internet is an important source of health information with relevant impact on the physician–patient relationship. The German urological associations host one of the most comprehensive platforms for patient information on urological diseases. The aim of the study was to characterise its users and their specific needs. We invited users of the websitewww.urologenportal.de via pop‐up to complete a 26‐item online survey to evaluate health‐related behaviour, distress and decision‐making preferences. We received n  = 551 complete responses. The most frequently requested topics were from the field of andrology (45.4%, n  = 250). Of these, the most popular topics were circumcision (28.9%, n  = 159) and erectile dysfunction (18.1%; n  = 100). Overall, 216 users (39.2%) searched for information prior to their first doctor's appointment, and 89.3% ( n  = 492) preferred autonomous or shared decision‐making. Users seeking information on circumcision were less frequently under urological treatment ( p  < .001), and more self‐determined regarding healthcare decisions ( p  = .01). Circumcision was the only information on the website, which received relevant critical comments. Andrology was the most frequently requested urological topic. The vast majority of patients wanted to take self‐determined healthcare decisions and searched for information prior to a doctor's appointment. This might have an impact on the physician–patient relationship and causes a high demand for good‐quality health information websites.